Strategic Energy Management and Carbon Footprint Reduction in University Campuses: A Comprehensive Review - Satish Suresh Tanavade; Ganesh Nagraj Patil; C. V. Sudhir; A. M. Saravanan (International Journal of Energy Economics and Policy, 2023)
This review paper offers a detailed analysis and summary of current studies related to energy management and carbon footprint reduction in university campuses. Using insights from different research papers, the review highlights the necessity for strategic and sustainable energy management approaches. The research reviewed explores a wide range of methodologies, including the examination of energy consumption, the identification of areas for improvement, the application of energy management and optimization techniques, and the use of renewable and sustainable energy strategies. It is evident from the review that successful energy management and carbon footprint reduction depend on energy management systems, integration of renewable energy, encouraging behavioural changes, and efficient resource use. The review paper is divided into six sections: understanding and enhancing energy consumption, Techniques for Energy Management and Optimization, random and systematic approaches to energy management, Energy Management Systems and their Applications, approaches for sustainable and renewable energy and carbon footprint reduction techniques. The review also identifies areas of future research in the field. It aims to serve as a valuable guide for university administrators, energy managers, and researchers seeking to implement sustainable energy practices and reduce carbon emissions on university campuses.